Arthropods (IntechOpen, 2023)
This book provides contributions on various topics pertaining to arthropods (insects and non-insects) written by experts in their respective fields. It targets a wide audience of entomologists, biologists, ecologists, zoologists, teachers, and students. The book is divided into four main sections on “Development”, “Food Detection and Feeding Behavior”, “Vector-borne Diseases”, and “Structure and Function of Vision”. Chapters address such topics as larval development and metamorphosis of non-insect arthropods, spatiotemporal dynamics of the silver leaf whitefly pest, the importance of three species of household cockroaches, lac insects that secrete resin worthy of industrial importance, the feeding behavior of some insects, and much more.